FREQUENCY OF EARLY ATRIAL FIBRILLATION IN POST MITRAL VALVE REPLACEMENT SURGERY - Waseem, Nayyar; ., Ikramullah; Khan, Ajab; Malik, Abdul; Khan, Riaz Anawr (Journal of Postgraduate Medical Institute, 2016)
Objective: To determine the frequency of atrial fibrillation after mitral valve replacement surgery. Methodology: This study was performed in cardiac surgery ward of Lady reading Hospital (LRH) Peshawar. It was a descriptive cross sectional study. Data was collected from 1.3.2014 to 28.02.2015. Statistical analyses were performed using SPPS version 14. Mean ± SD were used for quantitative and Frequencies and percentages were used for categorical variables. Results: Total 120 patients undergone through mitral valve replacement. Male patients were 48 (40%), Mean age of the study population was 46.20 years ± 9.14SD. Atrial fibrillation (AF) was observed in 45 (37.5%) patients. Post operative AF was similar between both gender and all ages. Conclusion: Atrial fibrillation is common finding in patients undergoing Mitral valve replacement surgery and is not affected by age and sex